Policy Implementation Hope Family Program in Allenging Poverty in Labuhanbatu District (in terms of muqashid sharia - Dewi Sartika Silalahi; Tuti Anggraini; Muhammad Arif (Budapest International Research and Critics University, 2022)
This article implements the policy of the family of hope program in tackling poverty in Labuhan Batu district. The aims of this research are: 1) How is the implementation of the policy of the family of hope program in tackling poverty in Labuhan Batu district? 2) what are the obstacles in overcoming the implementation of the policy of the family of hope program in tackling poverty in Labuhan Batu district? 3) What is the solution in the Islamic view of the economy? Implementation of the policy of the family of hope program in tackling poverty in Labuhan Batu district? The method in this study uses this type of research. Qualitative is descriptive. In order to obtain the required data, the researchers used techniques, including observation, interviews and documentation. Sources of information are the head of social empowerment, PKH coordinator, PKH operators, PKH recipient communities, and people who do not receive PKH. The results of the study found that: 1) The implications of providing financial assistance to the hopeful family program in the North Rantau sub-district are still not evenly distributed because many people in the North Rantau sub-district have not received PKH because there are many families who cannot afford it but have not been included in the list of PKH recipients. 2) Constraints in providing assistance to the family of hope program in North Rantau sub-district: a) Low knowledge of Beneficiary Families (KPM) about the PKH Family Hope Program. B) Lack of supervision from the government to control the implementation of PKH. 3) The solution in Islamic economics regarding the PKH program in overcoming poverty is linked to Maqasid sharia towards the provision of financial assistance for the family of hope program in North Rantau sub-district which has the aim of realizing human benefit by ensuring basic needs (al-dharurriyah), secondary needs (hajiyat), and complementary needs (thasiniyyat).